2022
DOI: 10.3390/insects13111072
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of dre4 Contributes to Mortality of Phyllotreta striolata

Abstract: The striped flea beetle, Phyllotreta striolata, is one of the most destructive pests of Cruciferae crops worldwide. RNA interference (RNAi) is a promising alternative strategy for pest biological control, which overcomes the weakness of synthetic insecticides, such as pest resistance, food safety problems and toxicity to non-target insects. The homolog of Spt16/FACT, dre4 plays a critical role in the process of gene transcription, DNA repair, and DNA replication; however, the effects of dre4 silencing in P. st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Third, more research is needed into incorporating natural enemies, including of EPNs and EPFs, into IPM programs and the role of habitat management in conservation biological control programs at local and landscape scales. Fourth, emerging technologies such as RNA interference, based on lethal genes found in SFB (39,58) and CSFB (37), should be explored to develop more specific biopesticides. Fifth, effective control of flea beetles requires the establishment of a comprehensive prediction and forecasting system.…”
Section: Discussionmentioning
confidence: 99%
“…Third, more research is needed into incorporating natural enemies, including of EPNs and EPFs, into IPM programs and the role of habitat management in conservation biological control programs at local and landscape scales. Fourth, emerging technologies such as RNA interference, based on lethal genes found in SFB (39,58) and CSFB (37), should be explored to develop more specific biopesticides. Fifth, effective control of flea beetles requires the establishment of a comprehensive prediction and forecasting system.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et. al silenced the dre4 gene using the technique of RNA interference and found that the silencing of dre4 contributed to the high mortality of CFB [ 21 ]. CFB adults have active, alert features and high tolerance to pesticides and live on the ground to feed on leaves, while the larvae hide in the soil and infest the seeds and roots.…”
Section: Discussionmentioning
confidence: 99%